Photosynthetic responses to understory shade and elevated carbon dioxide concentration in four northern hardwood tree species. - Sefcik, Lesley; Zak, D.R.; Ellsworth, D.S. (OXFORD UNIV PRESS, 2006)
Seedling responses to elevated atmospheric CO(2) concentration ([CO(2)]) and solar irradiance were measured over two growing seasons in shade-tolerant Acer saccharum Marsh. and Fagus grandifolia J.F. Ehrh. and shade-intolerant Prunus serotina, a J.F. Ehrh. and Betula papyrifera Marsh. Seedlings were exposed to a factorial combination of [CO2] (ambient and elevated (658 micromol mol-1)) and understory shade (deep and moderate) in open-top chambers placed in a forest understory. The elevated [CO(2)] treatment increased mean light-saturated net photosynthetic rate by 63% in the shade-tolerant species and 67% in the shade-intolerant species. However, when measured at the elevated [CO(2)], long-term enhancement of photosynthesis was 10% lower than the instantaneous enhancement seen in ambient-[CO(2)]-grown plants (P < 0.021). Overall, growth light environment affected long-term photosynthetic enhancement by elevated [CO(2)]: as the growth irradiance increased, proportional enhancement due to elevated [CO(2)] decreased from 97% for plants grown in deep shade to 47% for plants grown in moderate shade. Results suggest that in N-limited northern temperate forests, trees grown in deep shade may display greater photosynthetic gains from a CO(2)-enriched atmosphere than trees growing in more moderate shade, because of greater downregulation in the latter environment. If photosynthetic gains by deep-shade-grown plants in response to elevated [CO(2)] translate into improved growth and survival of shade-intolerant species, it could alter the future composition and dynamics of successional forest communities.